Diet and microbiota linked in health and disease. Issue 2 (7th February 2018) - Requena, T.; Martínez-Cuesta, M. C.; Peláez, C.
Abstract : Diet has shaped microbiota profiles through human evolution. Abstract : Diet has shaped microbiota profiles through human evolution. Traditional gut microbiomes are described to be driven by high levels of Prevotella . In the present, however, it is consistently described a lower microbial richness in urban industrialized populations compared with individuals living in rural settings, Bacteroides being predominant among urban-industrial gut microbiomes. Components of diet are highly influential in shaping the gut microbiota, being fiber, fat, proteins, polyphenols and micronutrients differentially metabolized by generalist and specialized microorganisms alone or through the phenomenon of cross-feeding. The progressive loss of microbial diversity over generations in industrialized societies along with the emerging increase of chronic non-transmissible diseases have been related to the decline in the consumption of dietary fiber. Diet and derived microbial metabolites have strong implications with the development of food associated diseases such as obesity and metabolic syndrome, malnutrition and eating disorders, intestinal inflammatory diseases and colorectal cancer, among others. Still, there is a need of further studies in order to identify microbiota-related biomarkers of risk for these disorders. In turn, healthy diets and specific nutritional interventions, including increase of dietary fiber and the consumption of probiotics and prebiotics, could be valuable for restoration of beneficial bacteria and microbiota diversity capable to shift from disease to health promoting states.